Pengaruh Idle Time Terhadap Produktivitas Kegiatan Bongkar Muat Curah Kering di Pelabuhan Java Integrated Industrial and Port Estate (JIIPE) (Studi Kasus PT Berlian Manyar Sejahtera Tahun 2024) - Wahyu Aria Prayoga; Bugi Nugraha; Prima Yudha Yudianto; Intan Sianturi (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to examine the effect of idle time on the productivity of dry bulk loading and unloading activities at the Java Integrated Industrial and Port Estate (JIIPE). The research employed a quantitative correlational approach, with data collection techniques including observation, documentation, and company records. The research sample consisted of 12 vessels engaged in loading and unloading at Java Integrated Industrial and Port Estate (JIIPE) port during the period from January to July 2024. The analysis revealed a correlation coefficient of -0.16, indicating a very weak negative relationship between idle time and productivity. The coefficient of determination, at 2.56%, suggests that idle time contributes only marginally to productivity, while the remainder is influenced by other factors. The factors affecting idle time include weather conditions, equipment failures, and truck delays. The conclusion indicates that while idle time does impact productivity, the effect is not statistically significant..